Parental attitudes in socialization and its relationship to the Value format among a sample of Damascus University students (Damascus University Journal of arts and humanities sciences, 2024)
The research aimed to identify parental attitudes in socialization and its relationship to the Value format in a sample of Damascus University students, the significance of the differences is defined according to the two variables: (sex, and academic specialization). It adopted the descriptive analytical method. The research sample was (239) male and female students, and the researcher used the parental attitudes scale in socialization and the Value format scale. The research concluded the following results: There is a statistically significant correlation between parental attitudes in socializationand the Value format among a sample of Damascus University students. There are no statistically significant differences between the average scores of the research sample's answers on the scale of parental attitudes in socialization, according to the two variables: gender and academic specialization. There are statistically significant differences according to the gender variable on the Value format scale in favor of females, and there are no statistically significant differences on the Value format scale according to the specialization variable.
Keywords: : parental attitudes in socialization; value system; university students.